Dorsal double layer dartos flap in the Snodgrass technique of hypospadias repair: An experience in Dhaka Medical College Hospital - Das, Sahadeb Kumar; Hasina, Kaniz; Huq, Md Ashraf Ul; Khan, Jaglul Gaffer; Alam, S M Shafiqul; Islam, Md Tawhidul (Journal of Paediatric Surgeons of Bangladesh, 2019)
Introduction: Hypospadias is one of the most common congenital anomalies and more than 300 operation techniques have been described for primary hypospadias. The Snodgrass technique and its modification have become a preferred for all varieties of hypospadias in the past decade. However fistula is the most common of this technique. The aim of the study is to investigate the importance of double layer dartos flap to prevent fistula formation in the Snodgrass technique. Materials and Methods: It’s a retrospective study, among 52 patients aged 11 months to 144 months who underwent mid penile and distal hypospadias repair in the Snodgrass technique using dorsal dartos flap for neo-urethral coverage. This study was done in the Department of Pediatric Surgery in Dhaka Medical College & Hospital from November 2014 to December 2016. Results: Urethrocutaneous (UC) fistula were encountered in 10 patients (19.23%), meatal stenosis in 3 patients (5.76%), partial glanular dehiscence in 1 patient and residual chordee in 1 patient. Conclusions: For preventing fistula formation, urethral covering by a well vascularized dorsal double layer dartos flap should be the important part of the Snodgrass technique. Journal of Paediatric Surgeons of Bangladesh (2017) Vol. 8 (2): 47-51